PERSONAL BRANDING UNTUK GENERASI Z: PELATIHAN BAGI SISWA SMA NEGERI 1 WONOSARI - Api Adyantari; Aloysia Desy Pramusiwi; Vonezyo Yupanzara Dharomesz (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aims to strengthen the soft skills and personal branding of Grade 10 Generation Z students at SMA Negeri 1 Wonosari, better preparing them for the transition to higher education and the workforce in the digital era. The program was implemented through four stages: (1) a needs assessment using observations and interviews with the student affairs unit, (2) selection of training content based on identified needs, (3) development of training modules covering key concepts, components, and practical steps in personal branding, and (4) interactive workshops featuring presentation practice, social media self-assessment, and direct feedback from the facilitation team. The results indicate that students were able to identify role models (influencers) and articulate reasons for following them that align with their interests and hobbies, while also recognizing the importance of maintaining a consistent self-image. Through guided practice and reflection, several students were able to express their unique strengths more clearly and confidently. Overall, the program contributed to improved communication skills, proactivity, and readiness for continuous self-development.